Empowering Caregivers to Improve Working Posture Management for Preventing Musculoskeletal Injuries in Long Term Care Settings - Indrayani, Ni Luh Dwi; Buntari, Ni Luh Putu Inca Agustini; Suyasa, I Gede Putu Darma; Sutini, Ni Kadek; Duygulu, Sergul; Portia, Vitug; Israfil, Israfil; Sagita, Ni Wayan Riska (Yayasan Ahmad Mansyur Nasirah, 2025)
Physically demanding tasks in long-term care, such as lifting and repositioning patients, increase caregivers' risk of musculoskeletal disorders, highlighting the need for empowerment through targeted education and skills training to ensure safe practices. This community service aimed to evaluate the effectiveness of an educational training program for caregivers, focusing on working posture management and technique in transferring older people to reduce the risk of musculoskeletal injuries. A pre- and post-intervention design was used to assess cognitive improvement and participant satisfaction among 41 caregivers in community setting. Results showed a marked increase in correct responses across all questionnaire items following the training, indicating improved knowledge and satisfaction throughout the training. The increased to 95.1% after the training was found, indicating a significant gain in knowledge about the basic concepts of transfer techniques. Participants expressed high satisfaction, with simulation-based learning identified as the most effective instructional method. The findings suggest that targeted, practical training can enhance caregivers’ competencies and contribute to safer caregiving practices. Despite these positive outcomes, limitations included a participant bias, limited follow-up, or the socio-economic context of the participants in short-term evaluation. Future programs are recommended to include follow-up assessments and wider community involvement to ensure long-term impact and sustainability.